The Effect of Two Dentin Bonding Agents on Microleakage of Ceramic Crown - Nadia M. Al-Shakir (University of Mosul, College of Dentistry, 2014)
Aims: The study aims to compare and investigate the effect of two bonding systems (total-etch and self-etch) bonding agents preceding the use of luting cement Variolink II Refill (Ivoclar Vivadent Schaan Liechtenstein) on the microleakage of ceramic crowns. The bonding systems compared are Excite (Ivoclar Vivadent Schaan Liechtenstein) (total-etch) and G bond (GC corporation, Tokyo, Japan) (self-etch) bonding agents. Materials and Methods: Thirty recently extracted caries-free wisdom teeth were used in this study. The teeth were cleaned and stored in distilled water until use. The molars were assigned randomly into three groups (n=10). Crown restorations were constructed by means of an indirect laboratory technique by a specialist. In group A the crown were cemented with Variolink II Refill resin luting cement alone. In group B, crowns were luted with Excite bonding agent +Variolink II Refill. In group C, G bond bonding agent+Variolink II Refill was applied prior to cementation. Results: The results showed that the higher value of microleakage with Variolink II Refill cement alone. While the least value was for the G bond+Variolink II Refill group. The results of this study revealed that the use of adhesives prior to Variolink II Refill significantly different from the use of Variolink II Refill alone in cementation of ceramic crown at (p< 0.05). Conclusions:` The analysis of results revealed statistical difference in microleakage between the first group (Variolink II Refill) cement and second ,third groups (Excite +Variolink II Refill) and (G bond + Variolink II Refill) respectively. This may indicate that, the use of adhesives prior to cementation with Variolink II Refill luting cement may decrease but not prevent microleakage.